The effect of temperature and soil moisture on carbon dioxide emission caused by various primary tillage methods in the Trans-Urals - E. A. Demin; S. S. Miller (Зерновое хозяйство России, 2025)
The purpose of the current work was to estimate the dynamic degree of the effect of temperature and soil moisture on the intensity of carbon dioxide emission when using various tillage methods. There has been studied the effect of tillage methods on the temperature regime and soil moisture under spring wheat crops in 2023–2024. There has been found that soil temperature and moisture greatly depend on weather conditions and ranged from 6.8–20.7 °C to 12.0–36.1 %. There has been determined that, depending on humidity and temperature, CO2 emission with moldboard plowing varied from 16.4 to 104.4 kg/ha per day from May to October, with subsoil plowing it ranged from 13.8 to105.7 kg/ha and with no-till method its range was from 8.8 to 94.2 kg/ha in 2023. In 2024, CO2 emission was larger and varied from 18.8 to 164.2 kg/ha with moldboard plowing, from 15.0 to 155.7 kg/ha with subsoil plowing, and from 12.0 to 142.5 with no-till method. The trial has established a high level of correlation between soil temperature and the rate of CO2 emission (r = 0.79–0.81). There has been determined that a 1°C increase in soil temperature increases daily CO2 emission by 9.44 kg/ha with moldboard plowing, by 9.59 kg/ha with subsoil plowing, and by 8.38 kg/ha with no-till method. There has been established a high level of correlation between soil moisture and emission (r = 0.58–0.67). There has been found out that a 1 % increase in soil moisture increases emission by 4.11 kg/ha with moldboard plowing and by 3.70 and 3.22 kg/ha with subsoil plowing and no-till method.